City Branding â€Shining Batuâ€ dan E-WOM serta Pengaruhnya terhadap Niat Berkunjung Wisatawan (Studi pada Wisatawan di Kota Batu) - Aleonita, Shelea; Andjarwati, Anik Lestari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
The purpose of this paper was to study the relationships among city branding, e-WOM (electronic word of mouth), and touristâ€™s intention for visiting. The study focused on the tourists who would visit Batu City as the sample by using a nonprobability sampling technique. Questionnaires were distributed to 200 participants by google forms. Data analysis techniques were Multiple Linear Regression with validity and reliability test, classic assumption, and hypothesis test (t-test). The results indicated that city branding is positively influenced by the touristâ€™s intention for visiting, but e-WOM is negatively influenced by the touristâ€™s intention for visiting. The implications in this study can be used as input for the Batu City Government in developing the city branding â€œShining Batuâ€ to increase touristâ€™s intention for visiting.